Final draft Arctic Offshore Oil and Gas Guidelines (2009). (DRAFT) - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment (PAME), 2008)
These Guidelines are intended to be of use to the Arctic nations for offshore oil and gas activities during planning, exploration, development, production and decommissioning Recommendations on the transportation of oil and gas are found in the OGA, 2008. The Guidelines should be used to help secure common policy and practices. The target group for the Guidelines is thus primarily the authorities, but the Guidelines may also be of help to the industry when planning for oil and gas activities and to the public in understanding environmental concerns and practices of Arctic offshore oil and gas activities. While recognizing the non-binding nature of these Guidelines, they are intended to encourage the highest standards currently available. They are not intended to prevent States from setting equivalent or stricter standards, where appropriate. Policy development should take into account the domestic situation with respect to political, economic, legal, and administrative conditions. Consideration should be given to macro-economic effects, regional effects, and potential environmental impacts. Such consideration should result in a staged opening plan, and ensure protection of areas of special environmental concern. While these guidelines do not address socio-economic aspects in any detail, nor do they set standards for assessment of potential socioeconomic effects of offshore oil and gas activities, these are nonetheless important to consider and integrate into the planning and conduct of exploration and development. The Guidelines are intended to define a set of recommended practices and outline strategic actions for consideration by those responsible for regulation of offshore oil and gas activities (including transportation and related onshore activities) in the Arctic (see Figure 1 and Annex A). It is hoped that regulators will identify the key aspects related to protection of human health and safety and protection of the environment for the management of offshore activities, while at the same time remaining ...